Picture books to help improve ESL learners' writing skills - Eng, Wei Chien; Lee, Lay Hui (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
This conceptual paper reports on the benefits of making picture books to help in improving English as second language learners’ writing skill. Writing skill is a language skill that needs to be learnt as it is a productive skill which used to communicate with other people effectively in form of words. In the Malaysian classroom, writing is an essential skill in English language learning which included in curriculum syllabus and being a part in writing test and examinations. However, for learners, completing writing task can be one of the drearier experiences for them. Instead of just interacting with words and letters, the learners prefer to interact with pictures. Picture books are amazing tools for education of young learners. Making picture book let the learners involve in a different way of writing experience either in learning the correct process of writing or do cooperative learning with peers. Pictures bring the writing to life which let them explore the ‘real world’ and inspire learners’ creativity and motivation. The whole process of making picture books brings enjoyment and excitement to the learners, which can sustain their involvement in the writing activity. Self- worth is also developed when they create their own production. In this paper, the authors discuss about using picture books in classroom and how it benefits the learners in improving their writing skills.